1995
DOI: 10.1126/science.267.5206.1966
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Visible Luminescence of Self-Assembled Semiconductor Quantum Dots

Abstract: Ensembles of defect-free InAIAs islands of ultrasmall dimensions embedded in AIGaAs have been grown by molecular beam epitaxy. Cathodoluminescence was used to directly image the spatial distribution of the quantum dots by mapping their luminescence and to spectrally resolve very sharp peaks from small groups of dots, thus providing experimental verification for the discrete density of states in a zero-dimensional quantum structure. Visible luminescence is produced by different nominal compositions of InxAI(1-x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
76
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(76 citation statements)
references
References 21 publications
0
76
0
Order By: Relevance
“…Au can become a good catalyst when present as small clusters [342] while as bulk matter it is the most inert material known to mankind [343]. Optical (see for instance plasmon excitations in small Ag particles [344,345]) and electronic properties (photoluminescence from quantum dots [346,347] and magnetism in metal clusters [348]) become widely adjustable through the particle size. Many of the physical and chemical properties can so far only be investigated with integrating techniques needing a considerable density of uniform particles.…”
Section: Discussionmentioning
confidence: 99%
“…Au can become a good catalyst when present as small clusters [342] while as bulk matter it is the most inert material known to mankind [343]. Optical (see for instance plasmon excitations in small Ag particles [344,345]) and electronic properties (photoluminescence from quantum dots [346,347] and magnetism in metal clusters [348]) become widely adjustable through the particle size. Many of the physical and chemical properties can so far only be investigated with integrating techniques needing a considerable density of uniform particles.…”
Section: Discussionmentioning
confidence: 99%
“…CL (in both SEM and TEM mode) has been utilized to image plasmon modes of particles and antennas of various shapes. [11][12][13][14] CL has been used in materials science as an advanced technique for examination of intrinsic structures of semiconductors such as quantum wells 15,16 or quantum dots 17,18 . Typically, a tightly focused beam of electrons impinges on a sample and induces it to emit light from a localized area down to 10-20 nanometers in size.…”
mentioning
confidence: 99%
“…Most previous optical studies of quantum dots (QDs) have probed large ensembles which have led to inhomogeneous broadening of the spectral features. However, recently several groups have shown that it is possible to study single QDs with photoluminescence (PL) either by reducing the size of the sample, [1] by cathodoluminescence [2,3], or by reducing the size of the laser spot on the sample through microscopic [4,5] or optical near-field techniques [6]. Here we use a similar technique whereby we combine high spatial and spectral resolution optics with excitation spectroscopy to study in detail the spectrum of a single QD [7].…”
mentioning
confidence: 99%